2015
DOI: 10.1523/jneurosci.3164-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Roles of Hydrophilic Loop 1 and the C-Terminus of Presenilin 1 in the Substrate-Gating Mechanism of γ-Secretase

Abstract: ␥-Secretase is a multisubunit protease complex that is responsible for generating amyloid-␤ peptides, which are associated with Alzheimer disease. The catalytic subunit of ␥-secretase is presenilin 1 (PS1), which contains an initial substrate-binding site that is distinct from the catalytic site. Processive cleavage is suggested in the intramembrane-cleaving mechanism of ␥-secretase. However, it largely remains unknown as to how ␥-secretase recognizes its substrate during proteolysis. Here, we identified that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 57 publications
6
45
0
Order By: Relevance
“…interacted with the TM of C99 and displayed high flexibility during the MD simulations indicating a role in substrate recognition. This corroborates earlier studies by Tomita et al [68] and is also partly evident from the cryo-EM structure of PS1-γ-secretase with C83 [19], although the thermal motions are expected top be much smaller at cryo temperature and thus possibly lead to only one bound conformation state.…”
Section: Individual Subunit Contributions To C99-γ-secretase Dynamicssupporting
confidence: 91%
“…interacted with the TM of C99 and displayed high flexibility during the MD simulations indicating a role in substrate recognition. This corroborates earlier studies by Tomita et al [68] and is also partly evident from the cryo-EM structure of PS1-γ-secretase with C83 [19], although the thermal motions are expected top be much smaller at cryo temperature and thus possibly lead to only one bound conformation state.…”
Section: Individual Subunit Contributions To C99-γ-secretase Dynamicssupporting
confidence: 91%
“…Subsequently performed post‐processing free energy calculations using molecular mechanics Poisson–Boltzmann surface area (MMPBSA) method (Genheden & Ryde, ) indicated that hNCT‐E242 indeed stabilizes GSEC‐APP/Aβ interactions by 2.90 ± 0.13 kcal/mol (mean ± SEM, with N = 1,500). Furthermore, the simulations supported the importance of the interactions between APP ectodomain and the first extracellular loop of PSEN1 (residues 109–118), a region reported previously to be involved in the substrate recognition (Takagi‐Niidome et al , ) and mutated in FAD.…”
Section: Resultssupporting
confidence: 74%
“…Substrate binding to HL1 is indispensable for both 3and g-cleavage, whereas binding to the C-terminal of PS1 hampers cleavage. 98 During the simulations, the RMSF of the catalytic aspartates is 0.17-0.28 nm (average 0.22 nm) and 0.12-0.15 nm (average 0.14 nm), respectively, for the Asp-263 and Asp-366, suggesting that the latter catalytic aspartate is much more restricted in its movement, which could be of catalytic relevance.…”
Section: Essential Dynamics Of Ps2-g-secretasementioning
confidence: 92%